Development of the concept of near-field technology in designing the effective small-aperture microwave antennas - Ivanchenko, I.; Popenko, N.; Khruslov, M.; Chernobrovkin, R.; Radionov, S.; Pischikov, V. (Радіофізика та електроніка, 2019)
Предмет и цель работы. Статья посвящена обзору публикаций авторов по исследованию эффективных малоразмерных одиночных излучателей различных типов с применением технологии ближних полей. Предмет і мета роботи. Статтю присвячено огляду публікацій авторів з дослідження ефективних малорозмірних одиночних випромінювачів різних типів із застосуванням технології ближніх полів. Subject and purpose. This article is devoted to the review of the original works of the authors on studying the effective small-sized individual radiators of various types using near-field technology.